Identificação de substância antimicrobiana produzida por Acinetobacter baumannii ativa contra amostras multidroga resistentes da bactéria - Natália Rocha Guimarães (2020)
Bacterial resistance is a global challenge. The search for new antimicrobials, mainly natural substances, has been gaining prominence due to the emergence of bacterial resistance to classic antimicrobial drugs. A. baumannii is a bacterium of great clinical relevance that expresses remarkable multidrug resistance and consequently is hard to control. The aim of this study was to identify an antimicrobial substance expressed by A. baumannii described during a previous study that demonstrated activity against multidrug resistant strains of the bacterium. In the first stage of this project, plasmid extraction was conducted to determine the location of the gene that codes for the substance. To confirm the results, heterologous expression in E. coli transformed with a wild plasmid was performed and evaluation of antagonistic activity by the double-layer diffusion and acid precipitation methods was done. The plasmid was sequenced (Illumina MiSeq) and similarity analysis using the BlastP was performed. In the second stage of the project the cloning of the ORFs was performed on TOPO and pET28aTEV vectors, with the aim to identify the gene that codes for the antimicrobial substance. The expression and purification of the recombinant proteins were evaluated by comassie stained SDS-PAGE and western blotting and evaluated by the double-layer diffusion method. The expression of the active protein was observed in a transformed E. coli BL21 system, confirming the presence of the gene of interest in the wild plasmid. The assembly of plasmid DNA generated a contig of 11,060 bp, with twelve ORFs. Similarity analysis allowed the small plasmid to be classified in the Rep-3 family, according to a RepB replication protein. Of the twelve ORFs annoted, five were suggestive of the substance. Based on data obtained throughout the development of the study, it is suggested that the hypothetical protein 3 is responsible for the antibacterial action observed against A. baumannii MDR strains.